Regulation of cytoskeletal dynamics by phospholipase D and phosphatidic acid - Pleskot, Roman; Li, Jiejie; Zárský, Viktor; Potocký, Martin; Staiger, Christopher J (Trends in plant science, 2013)
Plants respond to diverse biotic and abiotic stimuli as well as to endogenous developmental cues. Many of these stimuli result in altered activity of phospholipase D (PLD), an enzyme that hydrolyzes structural phospholipids producing phosphatidic acid (PA). PA is a key signaling intermediate in animals, but its targets in plants are relatively uncharacterized. Recent studies have demonstrated that the cytoskeleton is a major target of PLD-PA signaling and identified a positive feedback loop between actin turnover and PLD activity. Moreover, two cytoskeletal proteins, capping protein and MAP65-1, have been identified as PA-binding proteins regulating actin and microtubule organization and dynamics. In this review, we highlight the role of the PLD-PA module as an important hub for housekeeping and stress-induced regulation of membrane-associated cytoskeletal dynamics.
Keywords: Protein Binding; Plants; cytoskeleton; Actins; signaling; kyseliny fosfatidové; Phospholipase D; phospholipase D; signální transdukce; microtubules; Cytoskeleton; Plant Proteins; fyziologie rostlin; aktiny; Signal Transduction; Microtubules; rostliny; Stress, Physiological; vazba proteinů; fosfolipasa D; Cell Membrane; phosphatidic acid; Plant Physiological Phenomena; mikrotubuly; buněčná membrána; cytoskelet; actin; fyziologický stres; Phosphatidic Acids; rostlinné proteiny